Surgical options for the management of severe functional constipation in children. Issue 3 (June 2016) - Wood, Richard J.; Yacob, Desale; Levitt, Marc A.
Abstract : Purpose of review: Constipation is a very common problem in pediatrics with both the severity of presentations and treatments varying across a broad spectrum. The majority of children with functional constipation are managed successfully without the need for specialized testing and surgical intervention. Those who present with intractable constipation, with or without fecal soiling, require referrals for motility testing that helps determine both medical and surgical management, and interventions. The literature was reviewed for publications on surgical approaches to children with severe constipation, including assessing the quality and levels of evidence and the use of objective measures to determine outcomes. Recent findings: There is very little in the way of recent studies evaluating surgical indications or treatment approaches for functional constipation, apart from one systematic review and one recent expert review. Although the systematic review was published in the last year, most of the studies it analyzes are older. The vast majority of studies comprise level 4 and 5 evidence. Summary: The indication for most surgical procedures is 'failed' medical management, yet no standardized definition for this exists. Many surgical procedures are proposed with little evidence to show outcomes. We recommend that the surgical evaluation and treatment of children with constipation needs to be protocolized and studied in a prospective manner using validated outcomes measures. Our center's current protocol is described.